PTH-134 Transnasal Endoscopy in the Northern Region- Survey to Assess availability and Opinion of TNE. (4th June 2013) - Parker, C; Panter, S
Abstract : Introduction: Transnasal endoscopy (TNE) is performed with an ultrathin endoscope via the nasal passages. It has been available for over a decade and is widely used in Japan but use is variable in Europe and there is very little data on extent of use in the UK. It is recognised to have superior patient tolerability and satisfaction and there is emerging evidence that it causes significantly less cardiovascular upset. Anecdotally we perceive this method to be rarely used in our region and we performed a survey to assess extent of its use. Methods: This survey was to assess the availability of and opinion of TNE in the Northern region. The survey was circulated via email to the lead endoscopist in each of the 10 hospital trusts in the northern region. Opinion was sought on quality of views and biopsy samples and also perceived advantages and disadvantages of TNE. Results: Of the 10 surveys sent out all recipients responded. 2 trusts have access to TNE with only one trust having access to a specific TN service performing approximately 150–200 per year. The 2 trusts with access to TNE had both received training in TNE from industry and also in-house training. The trust with a TNE service had also received training from other endoscopists experienced in TNE and an ENT surgeon. When compared with standard endoscopy 30% thought views were worse, 60% the same and 10% unable to comment (due to lack of experience of TNE). 60% thought biopsy samples were adequate, 20% too small and 20% unable to comment. Advantages of TNE: 2 felt unable to comment due to lack of familiarity with this method. Improved patient tolerance was the main advantage stated by 7 with improved comfort, less gagging and reduced sedation requirements, with 1 stating less nursing support and therefore potential for evening lists and improving capacity issues as the main advantage. Disadvantages: 2 unable to comment, 2 no disadvantages, 2- stated cost of set up, 1- failure of nasal passage, 1-narrow channel limits therapy, 1-prolonged preparation time compared to throat spray and 1- poor views.7/8 without access to TNE felt a TNE service would be beneficial to their trust and 5 would be keen to set it up in their trust. Reported barriers to set up were cost 6/8 and time 1/8. 6 would be more likely to set up a TNE service if training were available. Conclusion: TNE is not widely used in our region with only 1 of 10 trusts performing regular TNE lists. It is perceived by the majority of endoscopists to have significant patient benefit and the majority are keen to set up a service. The main restriction to use appears to be the cost of set up despite the opinion that TNE is cost efficient overall. It is indicated that making TNE training available may increase its use. This was a regional survey and it would be interesting to see if these results are replicated nationally. Disclosure of Interest: C. Parker Grant/Research Support from: Submitting author's post is funded by Imotech Medical, S. Panter: None Declared